Molecular characterization and geographical distribution of Zika virus worldwide from 1947 to 2022 - Noisumdaeng P. (2023)
Objectives: We conducted molecular characterization, demonstrated the geographical distribution of Zika virus (ZIKV) circulating worldwide from 1947 to 2022 and explored the potential genetic recombination site in the Thailand ZIKV genomes. Methods: We constructed phylogenetic trees based on ZIKV coding sequences (CDS) and determined the geographical distribution of the representative viruses by genetic relationship and timeline. We determined genetic recombination among ZIKV and between ZIKV and other flaviviruses using similarity plot and bootscan analyzes, together with the phylogeny encompassing the CDS and eight subgenomic regions. Results: The phylogenetic trees comprising 717 CDS showed two distinct African and Asian lineages. ZIKV in the African lineage formed two sublineages, and ZIKV in the Asian lineage diversified into the Asian and American sublineages. The 1966 Malaysian isolate was designated the prototype of the Asian sublineage and formed a node of only one member, while the newer viruses formed a distinct node. We detected no genetic recombination in the Thailand ZIKV. Conclusion: Five Thailand isolates discovered in 2006 were the second oldest ZIKV after the Malaysian prototype. Our result suggested two independent routes of ZIKV spread from Southeast Asia to Micronesia in 2007 and French Polynesia in 2013 before further spreading to South American countries.